The Role Of Islamic Religious Education Teacher In Improving The Character And Islamic Behavior Of Students Of SMP Muhammadiyah 10 Surakarta - Firda Azaria Sarwinda Kusuma; Nurul Lathifatul Inayati (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2023)
This study aims to examine the role of Islamic religious education teachers in improving students' Islamic character and behavior at SMP Muhammadiyah 10 Surakarta. Through field research methods (field research), the author collected data through observation, interviews, and documentation at SMP Muhammadiyah 10 Surakarta. The results of interviews with Islamic religious education teachers show that character education based on PAI in this school is implemented holistically and involves all teachers. In addition to moral aqeedah lessons, character education is also carried out through the application of values in everyday life. Teachers use planned learning strategies and facilitated infrastructure to support student character education. Students exhibit good behavior in learning, and there is a relationship between good morals and good academic achievement. Even though there are some difficulties in implementing character education, such as the lack of support from students' parents, teachers still try to shape student character by relying on God for the results. In conclusion, Islamic religious education teachers at SMP Muhammadiyah 10 Surakarta have an important role in shaping students' Islamic character and behavior. Through the strategies and practices they employ, students can develop a better understanding of the Islamic religion and apply it in their daily lives.